1992
DOI: 10.2337/diacare.15.5.632
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Proinsulin Levels Related to Islet Cell Antibodies in First-Degree Relatives of IDDM Patients

Abstract: Fasting proinsulin concentrations were raised not only in siblings but also in parents and children of IDDM patients. Because proinsulin is more elevated in ICA+ than in ICA- subjects, increased proinsulin levels could reflect minor beta-cell damage due to previous immunological attack.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
1
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 0 publications
5
20
1
1
Order By: Relevance
“…Indeed, our data show a marked increase in the proportion of newly synthesized proinsulin after 48 h IL-1b treatment. These islets have previously been shown to have decreased insulin release in response to glucose and decreased insulin and DNA content (Bendtzen et al 1986, Sandler et al 1987, Spinas et al 1992. Our results are in line with previously published data, indicating decreased conversion rate in rat islets after 24-h IL-1b (Hansen et al 1988) and that exposure of b-cells to IL-1b for 24 h suppresses both proinsulin biosynthesis as well as the expression of PC2 by 46% via an NO-mediated pathway (Zambre et al 2001).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, our data show a marked increase in the proportion of newly synthesized proinsulin after 48 h IL-1b treatment. These islets have previously been shown to have decreased insulin release in response to glucose and decreased insulin and DNA content (Bendtzen et al 1986, Sandler et al 1987, Spinas et al 1992. Our results are in line with previously published data, indicating decreased conversion rate in rat islets after 24-h IL-1b (Hansen et al 1988) and that exposure of b-cells to IL-1b for 24 h suppresses both proinsulin biosynthesis as well as the expression of PC2 by 46% via an NO-mediated pathway (Zambre et al 2001).…”
Section: Discussionsupporting
confidence: 92%
“…Combining these observations with their findings in the study with long-term discordance for IDDM (2), the authors concluded that the changes in B cell function, characterised by increased fasting PIM concentrations, do not necessarily progress to diabetes (19). However, we have previously found greater PIM concentrations in relatives with ICA, even though also the ICA-negative relatives had increased PIM concentrations compared with those in unrelated controls (9). The fact that HLA sharing is not associated with increased PIM concentrations speaks against a dysfunction of the B cells that would progress to IDDM in siblings with increased concentrations of PIM (1, 3).…”
Section: Discussionsupporting
confidence: 52%
“…The increased PIM in healthy siblings of patients with IDDM could be an indicator for risk of progression to IDDM, but this is unlikely, as the twins and siblings (1,2) were discordant for several years, and there was no difference in PIM concentrations between HLA-identical, haploidentical and non-identical siblings (1). Islet cell antibodies (ICA) have been observed to be associated with increased PIM concentrations (9), but most of the first-degree relatives in previous studies tested negative for ICA (1,2,9). However, in some siblings we found increased PIM concentrations or PIM/C-peptide ratios associated with decreased B cell function and later progression to IDDM (10).…”
Section: Introductionmentioning
confidence: 99%
“…Up to a 500-fold excess of C-peptide did not interfere in the proinsulin assay. Because of high crossreactivity with conversion intermediates [74% for split (32)(33) proinsulin, 65% for des (31,32) proinsulin, 78% for split(65-66) proinsulin and 99% for des(64,65) proinsulin], the assay was considered to measure total proinsulin immunoreactive material [27]. It comprises two separate overnight incubations allowing the monoclonal antibodies used in the assay to compete with IAA (if present in the plasma tested) for binding to proinsulin.…”
Section: Methodsmentioning
confidence: 99%